The role of socio-cultural background and child age for parental regulation strategies and children's self-regulation: a comparison between Germany, Chile, and El Salvador - Mata, Cecil; Pauen, Sabina (Acta psychologica, 2023)
This study compared parental regulation strategies and children's self-regulation in three different countries (Germany, Chile, El Salvador). N = 300 primary caregivers of 1- to 3-year-olds filled out a parental questionnaire (IMpulse-MAnagement in the caregiver-child dyad, IMMA; Pauen et al., 2019) assessing (a) socio-demographic variables, (b) parental ideas and goals regarding children's self-regulation skills, (c) children's self-regulation strategies in dealing with internal challenges or demands, and (d) caregiver's regulation strategies. Age-group comparisons revealed that (1) children increased compliance and verbal negotiation with their caregivers as they grow older, and (2) parents adapted their regulation strategies to the age of the child. Country-group comparisons further indicated substantial similarities and differences between countries with respect to (3) how parents expected children to deal with requests and prohibitions, as well as with their own needs, feelings, and impulses, (4) how children responded to goal-frustration and parental demands, and (5) which regulatory strategies parents used to support their offspring. These exploratory findings are discussed in the light of current models on cultural learning, parent-child interactions, and child self-regulation development.
Online verfügbar 24 February 2023, Version des Artikels 24 February 2023
Gesehen am 10.07.2023